Alkali-catalyzed supercritical water gasification of sewage sludge: effect of liquid residue reuse as homogenous catalyst - Zhang, H.; Zhang, S.; Weng, Zhouchao; Mubeen, Ishrat; Zhang, C.; Yan, Mi; Fauziah, Shahul Hamid (Springer Verlag, 2020)
Conventional supercritical water gasification (SCWG) of sewage sludge produces liquid residues with organic pollutants, heavy metals and others. In order to reduce liquid residues released into the environment, this study investigated the reuse of liquid residues as feed water in subsequent SCWG. We also evaluated the effect of wastewater reuse on syngas production and fate of heavy metal. The experiment was performed in a 500-ml-capacity Hastelloy reactor at 400 °C and above 25 Mpa for 60 min with a 4:1 ratio of 10% dry wt. of solid (mixture of sludge and empty fruit bunch) and 90% wt. of liquid feed. The use of recycled liquid increased the concentration of K and Na in the solution from 26 mg/L and 91 mg/L to 49 mg/L and 290 mg/L, respectively. Subsequently, syngas production increased from 9.4 to 14.1 mol/kg organic matter. In addition, H2 production increased by 30%. The increase in syngas generation could be attributed to the alkaline salts which act as homogenous catalysts and to the organic matter in the liquid residue. In addition, the total mass of As, Cr, Cd, Cu, Pb and Zn in the liquid residues reduced from 57.36 to 47.34 µg. Thus, experimental results imply that the recycling of liquid residues in SCWG will not only improve the syngas production efficiency of the system, but also enable the accumulation of heavy metals in the solid residue to prevent pollution risk. © 2020, Islamic Azad University (IAU).